Adaptive reuse of heritage timber building : the need of modern technology / Juliza Mohamad - Mohamad, Juliza (2012)
This article is about a study on adaptive reuse of heritage timber building in consideration of technical aspects. In Malaysia, it is estimated that there are only a few numbers of heritage timber building such as palace, mosque and Malay traditional houses left. Some of the heritage timber buildings were damaged because of lack of maintenance and few were abandoned, and there were also few buildings were burnt down. A few numbers of heritage timber buildings were converted their function into a new function. The characteristics of heritage timber buildings which were built to response with the climatic conditions need to be adjusted to adapt new modern technology in consider to fulfil the requirement for a new function. The aim of this paper is to find solution on how to adapt then new requirement, i.e. new modern technology such as electricity, air-conditioning system and water plumbing system to the heritage timber buildings which have been converted into another building function to make the building well functioned without giving the negative impact to the old buildings.